رقابة القضاء الدستوري على تعديل الدستور (مجلة جامعة بابل للعلوم الانسانية, 2018)
The subject of the research revolves around the extent to which the constitutional judge has the authority to supervise the amendment of the constitution and the extent to which the constitution grants this jurisdiction to the constitutional judge. There is a difference in the position of the constitutions towards this subjectbut even the constitutions granted by the constitutional judge this jurisdiction have also differed in the form of censorship granted to him to amend the provisions of the constitution between the previous censorship of the amendment of the texts as one of the procedures of amending the constitution to be presented to the constitutional judge as a precautionary measure to prevent violation of the competent authority to amend the restrictions amendment of the Constitution or Subsequent control of the amendment of the Constitution The scope of this control, whatever its type and form, varied to include the control of both substantive and formal restrictions, or only one of them, where the constitutions differed in their position on this issue.